Nursing Care of Clients Who Have Nutritional Deficits with Type 2 Diabetes Mellitus in RSAU dr. Esnawan Antariksa East Jakarta: Siti Maulindah Hafidzha, Revie Fitria Nasution - Hafidzha, Siti Maulindah; Nasution, Revie Fitria (Jurnal Persada Husada Indonesia, 2020)
Diabetes Mellitus is a set of metabolic disorders characterized by elevated blood glucose levels (hyperglycemia) due to damage to insulin secretion, insulin process or both. Based on research of data obtained from medical record at RSAU dr. Esnawan Antariksa Jakarta Timur in November and December 2017 Diabetes Mellitus is included in the highest number who get a percentage of 14.65%. While there were 7 people or about 15.05% of diabetes mellitus clients from 30 clients in Merpati space during the study. This case study is to describe the implementation of nursing care on clients who have nutritional deficits with diabetes mellitus in RSAU dr. Esnawan Antariksa East Jakarta. The research design used was qualitative descriptive with intervention through case study approach. Participants in this case study include clients, families, and nurses, to medical diagnosis and nursing the same problems that clients who have nutritional deficits with diabetes mellitus. The main interventions performed on both clients are an observation of nutritional intake and weight weighing. The results show on both clients, nutritional deficit problems can be overcome by weight gain, good client appetite, and no signs of nutrient males in both clients.